RESPIRATORY AND RENAL INSUFFICIENCY AS RISK FACTORS OF SURGICAL TREATMENT OF PATIENTS WITH AORTIC ANEURYSM OF THE INFRARENAL SEGMENT - N. A. Yaitsky; A. Ya. Bedrov; G. I. Martynenko; A. A. Vraby; A. A. Moiseev (Вестник хирургии имени И.И. Грекова)
Retrospective analysis of data in 188 patients showed, that chronic nonspecific pulmonary disease was diagnosed in 65,4 % of all. Disorders of bronchial patency of different degrees of manifestation were noted in 61,2 % and 19,7 % of patients had a hypoxemia. Renal diseases were found in 59 % of patients, resulting in the development of chronic renal insufficiency in 17 %. The data obtained indicate, that the presence of coexisting pulmonary pathology directly influences the frequency and severity of respiratory complications after surgery, which can be the cause of fatal outcome. The presence of renal diseases results in three times higher risk of the development of postoperative renal complications.